The Question of Public Criminology: Seeking Resources of Hope for a Better Politics of Crime. (2014) - Loader, Ian; Sparks, Richard
Summary: This paper develops an argument lightly sketched in our book Public Criminology? (2010). There we posed the question of what it would take for criminology to make a substantial contribution to the search for "a better politics of crime". We were of course well aware of what some of our critics then informed us, namely that this was just a suggestion in need of much fuller articulation. Here we begin by summarizing the position outlined in that book and some subsequent papers. We argue that criminology has indeed made some salient contributions to the search for a better politics, but the scale of that contribution has also been limited by some intellectual tendencies that draw energy and attention away from the kind of reconstruction that we propose. In particular, the tone of some of the leading accounts of recent penal politics is grim — not without reason, as we freely acknowledge. If the trends with which we have become so familiar in some parts of the world — chronically high levels of incarceration, racial disproportion, demotic symbolic politics — flow either from core features of 'late modernity' or from inherent logics of neoliberal globalization, as some key contributors have insisted, then the prospects for changing these in any substantial and purposeful way, any time soon, seem rather slim. There have of course been reversals in the unremitting rise of mass incarceration recently. Are these more than temporary, reversible fluctuations? Are some of those who celebrate them clutching at straws? It is not necessary to share such (perhaps premature) optimism to wish to promote a somewhat different and more hopeful form of analysis and engagement. Is there perhaps also an opposite tendency to depict some of these problems as so massive and intractable — the tendency that we here call 'hype' — as to deter us from practical intervention? This paper seeks to identify some resources that could contribute to the task of reconstructing our approaches to theorizing our institutions and practices of crime control. If criminology is to contribute more effectively to thinking about how we draw limits to state coercion and demand strict scrutiny over the threats to individual rights, human development, and civic dignity posed by institutionalized exclusion and stigmatization it will need access to a certain range of perspectives and to build (or re-build) some alliances. What kind of criminology is best suited to the challenge of developing penal practices and institutions fit for democratic societies?